Publicly Financed Education in an Endogenous Growth Model - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2002)
This paper constructs an endogenous growth model, applicable largely to developing countries, based on human capital accumulation in which education is publicly provided and financed, and schooling is compulsory. Public investment in human and physical capital are financed from taxes on wage and capital income, and consumption. The equilibrium growth properties of the model are examined and the steady-state effects of education and fiscal policy are derived. The specification of the human capital production function and the strength of labour supply effects are shown to be important for the magnitude of steady-state outcomes. Simulations illustrate the model's properties.
Keywords: H52; H2; H4; D5; 330; Education; Taxation; Endogenous Growth; Labour Supply; General Equilibrium